Modeling and computation in engineering III : proceedings of the 3rd International Conference on Modeling and Computation in Engineering (CMCE 2014), Wuxi, China, 28-29 June 2014 /: proceedings of the 3rd International Conference on Modeling and Computation in Engineering (CMCE 2014), Wuxi, China, 28-29 June 2014. ([2014]) - Unknown
No abstract available